Persepsi Risiko dan Keputusan Investasi pada Generasi Z: Studi Komparatif Mahasiswa Ekonomi dan Non-Ekonomi di Kota Makassar - Idrus, Mukhammad (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to examine the differences in risk perception and investment decision-making among students with economic and non-economic academic backgrounds in Makassar City. Employing a quantitative approach and utilizing independent sample t-tests, the research collected responses from 90 students representing both disciplines. The results indicate that there are no statistically significant differences in either risk perception or investment decision-making between the two groups (p > 0.05). These findings suggest that academic background does not substantially influence students’ investment behaviors, which may instead be shaped by individual experiences, access to financial education, and exposure to investment-related content through digital platforms. The study highlights the growing role of financial information accessibility in bridging knowledge gaps across disciplines and underscores the need for inclusive financial literacy programs at the university level. These programs should target students from all academic areas to foster sound financial decision-making among youth. This research contributes to the understanding of behavioral finance among the young generation in emerging economies and calls for further studies with broader samples and multi-factorial models.